Farming fit? Dispelling the Australian agrarian myth - McCoombe Scott; Chandrasekara Ananda; Brumby Susan; Kremer Peter; Lewandowski Paul (BMC Research Notes, 2011)
Abstract Background Rural Australians face a higher mental health and lifestyle disease burden (obesity, diabetes and cardiovascular disease) than their urban counterparts. Our ongoing research reveals that the Australian farming community has even poorer physical and mental health outcomes than rural averages. In particular, farm men and women have high rates of overweightness, obesity, abdominal adiposity, high blood pressure and psychological distress when compared against Australian averages. Within our farming cohort we observed a significant association between psychological distress and obesity, abdominal adiposity and body fat percentage in the farming population. Presentation of hypothesis This paper presents a hypothesis based on preliminary data obtained from an ongoing study that could potentially explain the complex correlation between obesity, psychological distress and physical activity among a farming population. We posit that spasmodic physical activity, changing farm practices and climate variability induce prolonged stress in farmers. This increases systemic cortisol that, in turn, promotes abdominal adiposity and weight gain. Testing the hypothesis The hypothesis will be tested by anthropometric, biochemical and psychological analysis matched against systemic cortisol levels and the physical activity of the subjects. Implications of the hypothesis tested Previous studies indicate that farming populations have elevated rates of psychological distress and high rates of suicide. Australian farmers have recently experienced challenging climatic conditions including prolonged drought, floods and cyclones. Through our interactions and through the media it is not uncommon for farmers to describe the effect of this long-term stress with feelings of 'defeat'. By gaining a greater understanding of the role cortisol and physical activity have on mental and physical health we may positively impact the current rates of psychological distress in farmers. Trial registration ACTRN12610000827033